Using Paleolimnology for Lake Restoration and Management - Isabelle Larocque-Tobler (Frontiers Research Topics, 2017)
This e-book presents state-of-the-art research projects and opinions on using paleolimnology for lake restoration and managment. It illustrates the general idea that proposing adequate restoration and managment solutions must be based on the past. Knowing the natural and anthropic variations a water body went through defines the best ways for maintaining or restoring an ecosystem. By quantifying baseline conditions, paleolimnology provides a definite plan for restoration and management. This cannot be achieved without studying the past.